Pumping station design - Jones, Garr M.; Bosserman, Bayard E.; Sanks, Robert L.; Tchobanoglous, George (Amsterdam ; Boston : Elsevier/Butterworth-Heinemann, 2008)
Pumping Station Design, 3rd is an essential reference for all professionals. From the expert city engineer to the new design officer, this book assists those who need to apply the fundamentals of various disciplines and subjects in order to produce a well-integrated pumping station which is reliable, easy to operate and maintain, and free from design mistakes. The depth of experience and expertise of the authors, contributors, and peers reviewing the content as well as the breadth of information in this book is unparalleled making this the only book of its kind. * An award-winning reference work that has become THE standard in the field * Dispenses expert information on how to produce a well-integrated pumping station that will be reliable, easy to operate and maintain, and free from design mistakes * 60% of the material has been updated to reflect current standards and changes in practice since the book was last published in 1998 * New material added to this edition includes: the latest design information, the use of computers for pump selection, extensive references to Hydraulic Institute Standards and much more!
Introduction; Nomenclature; Flow in Conduits; Piping; Valves; Fundamentals of Hydraulic Transients; Control of Hydraulic Transients; Electrical Fundamentals and Power System Principles; Electrical Design; Performance of Centrifugal Pumps; Types of Pumps; Pumps: Selection, Installation, & Intakes; Electric Motors; Engines; Variable-Speed Pumping; Pump-Driver Specifications; System Design-Wastewater Pumping; System Design-Water Pumping; System Design-Sludge Pumping; Instrumentation & Control Devices; Instrumentation & Control Applications; Vibration & Noise; Heating, Ventilating & Cooling; Designing for Easy Operation & Maintenance; Station Layout; Avoiding Blunders; Contract Documents; Costs; App.
Includes bibliographical references and index.
Keywords: Pumping stations -- Design and construction; Water treatment plants; Sewage disposal plants; Electronic books